PERSONALITY, TRAITS, GENDER AND INFORMATION COMPETENCY AMONG COLLEGE STUDENTS - Nahyun, Kwon; Hana, Song (Malaysian Journal of Library and Information Science, 2017)
This study examines the influence of personality traits on information competency. Furthermore, it seeks to determine whether or not gender moderates the relationship between personality traits and information competency. Data were collected using standardized survey instruments, including Costa and McCrae’s NEO-Five Factor Inventory. The surveys were administered to a convenient sample of 185 college students at a large public university in the southeastern United States. The study results show that three of the five personality traits were significant determinants of information competency among the population sample. Those students, who are more conscientious, open to experience, and extroverted tended to report greater information competency than students who are not. Neither neuroticism nor agreeableness was identified as determinants. Revealing the moderating role of gender, the study uncovers gender-specific personality traits that affect information competency. Specifically, the study finds extroversion to be a male-specific trait and openness to experience a female-specific trait. The results identify conscientiousness as the most consistent and robust determinant of information competency across both genders. The concluding analysis relates the findings’ implications to information literacy.